Comparative Study on Disclosure of Islamic Social Reporting (ISR) Based on the ISR Index between Islamic Banking in Asia and Africa - Anita Mariana; Warno Warno; Firdha Rahmiyanti (AL-ARBAH: Journal of Islamic Finance and Banking, 2023)
Purpose - This study aims to compare the level of disclosure of Islamic Social Reporting between Islamic banking in Asia and Islamic banking in Africa using the ISR index approach.  Method - The data analysis in this study used content analysis. The sample in the study was 18 Islamic Commercial Banks with purposive sampling method.Result - The results of the study show that there are differences in the implementation of social performance of Islamic banking in Asia and Africa. This is proven by the results of the Mann Whitney test with a sig value of 0.001 greater than α = 5%. There is some evidence that of all Islamic banks, both Asian and African, none has yet achieved 100% (one hundred percent) implementation and disclosure of the ISR Index.Implication - This research uses secondary data in the form of annual reports and annual financial reports on the respective official websites of Islamic Commercial Banks in Asia and Africa during the 2012-2020 period.Originality- Further research is expected to be able to use or add variables and increase the research sample so as to obtain results that better describe the actual situation.